Teatterista valkokankaalle : Hella Wuolijoen näytelmien ja elokuvasovitusten vertailua - Ammondt, Jukka (1986)
Hella Wuolijoki (1886-1954) is one of the best known Finnish playwrights. Estonian by birth, she started her literary career in her native language, and it was not until 1936 that she made a definite decision to write only in Finnish. Hella Wuolijoki is a central figure also in the history of Finnish film making, as all the nine plays which she wrote using the pen name Juhani Tervapää and which all enjoyed great popularity in Finland have been made into films.